PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN APLIKASI JAMBOARD TERHADAP KEMAMPUAN ARGUMENTASI SISWA SEKOLAH DASAR - Rosmayanti; Hayati Rahayu, Ai; Titi Setiawati (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research is motivated by the weak argumentation skills of students, especially in the subject of Science (specifically on water quality topics). This issue arises from students' relative lack of understanding of argumentative questions, leading them to rarely apply their argumentation skills in class. The aim of this study is to determine the influence of problem-based learning model assisted by the jamboard application on argumentation skills of fifth-grade students at SDN Pakuwon I. The method employed is pre-experimental, with the research design being a one-group pretest-posttest design. Data collection techniques include observation and written tests. Data analysis for observations uses a checklist format and rating scales, calculated by percentage. For test results, normality tests (Lilliefors test) and t-tests are used. Based on the analysis, the average argumentation skills of the students are at level 1, indicating good quality of argumentation skills. Statistical analysis using the t-test shows a p-value of 0.00007 with α=0.05. Since the p-value is less than 0.05, H0 (null hypothesis) is rejected, and H1 (alternative hypothesis) is accepted. Therefore, it can be concluded from this research that the problem-based learning model assisted by the jamboard application has an influence on students' argumentation skills.